2015
DOI: 10.1002/ls.1291
|View full text |Cite
|
Sign up to set email alerts
|

Ferrofluids lubrication: a status report

Abstract: Ferrofluids (FFs) are stable colloidal suspensions composed of single‐domain magnetic nanoparticles dispersed in a carrier liquid. And it is an intelligent material, exhibiting normal liquid behaviour coupled with superparamagnetic properties. Since the properties and the location of these fluids can easily be influenced by a magnetic field, FFs have recently attracted many scientific, industrial and commercial applications. Lubrication is one of the most important applications for FFs, and the advantage of FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 92 publications
0
27
0
Order By: Relevance
“…In medicine, shaft seals for rotary blood pumps with low friction requirements are critical for micro leakage and long-lasting usage. Magnetic fluid seals seem perspective for these applications with their zero leakage, no wear, and constant density and viscosity properties [1][2][3][4]. A magnetic fluid sealing system can work together with magnetic bearings in one hybrid device being a common seal and bearing kit.…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, shaft seals for rotary blood pumps with low friction requirements are critical for micro leakage and long-lasting usage. Magnetic fluid seals seem perspective for these applications with their zero leakage, no wear, and constant density and viscosity properties [1][2][3][4]. A magnetic fluid sealing system can work together with magnetic bearings in one hybrid device being a common seal and bearing kit.…”
Section: Introductionmentioning
confidence: 99%
“…The brief study of above applications can be had from (Scherer and Figueiredo Neto, 2005). Huang and Wang (2016) prepared a review report on the progress of ferrofluid lubrication based on the three flow models of Neuringer-Rosensweig, Shliomis and Jenkins. They have briefly discussed some experimental studies on ferrofluid lubrication and concluded that over the conventional lubricant ferrofluid have considerably better friction decline and anti-wear abilities under the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrofluid or magnetic fluid is a stable colloidal suspension of small particles of ferromagnetic material in a carrier liquid. For us to avoid agglomeration from van der Waals and magnetic attractions, the ferromagnetic particles have to be coated with a surfactant . When a magnetic field is applied to the ferrofluid, each particle experiences a magnetic body force depending on the particles magnetization and on the strength of the applied magnetic field .…”
Section: Introductionmentioning
confidence: 99%